IMPROVING THE METHODOLOGY OF USING THE INTEGRATION OF INFORMATION COMMUNICATION AND PEDAGOGICAL TECHNOLOGIES IN THE TEACHING OF ANALYTICAL CHEMISTRY (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article explains the improvement of the methodology of using the integration of information communication and pedagogical technologies in teaching the science of "Analytical Chemistry". The article describes information and pedagogical technologies, integration, the meaning of integrated education and their content.